Field trial of Cyromazine (CGA-72662) as a feed additive to control breeding of flies in cattle manure - M. Fadzil ,; A. R., Ahmad Nazri (Malaysian Society of Parasitology and Tropical Medicine, 1988)
CCA-72662 was tried as a feed additive in cattle. At a concentration of 15 ppm and above it was able to suppress development of fly larvae after 17 days of medication. An average daily weight gain was recorded.